Association and outcomes of vf according to involved coronary artery in STEMI – a nationwide analysis. (3rd October 2022) - Seri, A; Baral, N; Kambalapalli, S; Khan, M; Paul, T
Abstract: Background: Ventricular fibrillation (VF) is common in acute ST segment elevation myocardial infarction (STEMI) and is associated with increased in-hospital mortality rate. Purpose: We sought to investigate the association between VF and artery involved in STEMI Methods: This is a retrospective observational study of hospitalizations between January 1, 2016 and December 31, 2019, using the National Inpatient Sample (NIS), the largest all-payer public database of hospital care in the United States. Results: A total of 138, 201 patients were primarily hospitalized for STEMI from 2016 to 2019. Among them 12, 318 had right coronary artery (RCA) lesions, 427 had left main (LM) lesions, 2381 had left circumflex (LCx) lesions and 12, 765 had left anterior descending (LAD) lesions. Mean age of patients with VF and STEMI was 62 years and that with RCA (63 years), LM (65 years), LCx (62 years), LAD (60 years), p<0.001. Females were 30.5% (n=42, 231) among all STEMI group and 29.8% (n=3672) RCA, 29% (n=124) LM, 27.4%(n=653) LCx and 28.6%(n=3645) LAD, p<0.001. In-hospital mortality for all patients with STEMI was 7.9%. The in-hospital mortality associated with STEMI there was 5%, 23.4%, 6.6%, 7.1%, (p<0.001) for RCA, LM, LCx and LAD respectively. The incidence of VF among all patients with STEMI was 8.3% (n=11425) and for LM, LAD, LCX, and RCA was 12.9%, 10.7%, 9.2% and 7.9% (p<0.001). Mean hospital length of stay for VF with RCA (6.2 days), LM (5.5 days), LCx (6.9 days) and LAD (7.4 days). After adjusting for age, gender, race, income, comorbidities, hospital teaching status, region and year, patients with STEMI who had VF had higher odds of mortality (aOR 6.4, 95% CI, 6.1 to 6.8; P<0.001). The highest likelihood of mortality observed in patients with VF who had and LCx STEMI (aOR 7.9, CI 95%, 5 to 12.4; p<0.001) followed by RCA STEMI (aOR 7.4, 95% CI 6 to 9.1; p<0.001), and LM STEMI (aOR 6.1, 95% 3.1 to 12; p<0.001). Conclusion: Highest in-hospital mortality was observed in patients with STEMI who had VF in LCx, followed by RCA and LM. There was higher occurrence of VF in STEMI involving LM. Funding Acknowledgement: Type of funding sources: None.